A Framework That Describes the Challenges of the High Jewelry Market in the US. Issue 3 (2nd September 2018) - Serdari, Thomaï; Levy, Jennifer
Abstract: The fine jewelry market took a major hit during the financial crisis of 2008–2010. Even though jewelry sales increased when the economy recovered and boosted consumers' confidence, today fine jewelry faces additional challenges that relate to other than economic forces. The American market, one of the strongest in the consumption of luxury, is also the one that offers signals of change in how a new generation of consumers wish to wear, purchase, and invest in the jewelry sector. Based on original market research, the following paper proposes a new framework for performance evaluation of existing competitors as well as for ideas on how to strategize for the future.